Superficial lymphatic drainage of the vulva and its relation to the regional nodes: an experimental study - Pavlista, D; Eliska, O (Folia morphologica, 2022)
BACKGROUND: Sentinel node biopsy in vulvar cancer is associated with much less morbidity than inguinofemoral node dissection. Our study focused on describing the morphology of superficial lymphatic drainage of the vulva and its relationship to regional nodes, which may facilitate orientation during surgery. MATERIALS AND METHODS: In 24 female cadavers, injections of patent blue (at various localisations medially, unilaterally and bilaterally) were used to visualise the lymphatic drainage of the vulva. After dissection of lymphatic vessels and nodes, their course was documented by photograph and then analysed. Subsequently, a map of vulvar superficial lymphatics was created. RESULTS: The cutaneous and subcutaneous tissue of the vulva primarily drained to superficial inguinal nodes. There was no evidence of a solitary lymph node that drained the unilateral vulva. Each area of the vulva drained to its own lymph node, which was variably localised in the subcutaneous groin around the great saphenous vein. Anastomoses between individual inguinal superficial lymph nodes are likely. Right-left symmetry in the course of lymphatic collectors was not detected. Natural drainage of the medial and paramedial areas to contralateral inguinal nodes was also not detected. The drainage pattern to ipsilateral inguinal nodes was consistent in cadavers without evidence of vulvar disease and may be applicable in the early stages of vulvar cancer. CONCLUSIONS: There was no evidence of a solitary node that drained the unilateral vulva. Each part of the vulva may drain to a corresponding lymph node in a different localisation of the groin. The surgeon should take this variability into account.
Keywords: Lymph Nodes; lidé; Sentinel Lymph Node Biopsy; Lymphatic Vessels; lymfatické uzliny; biopsie sentinelové lymfatické uzliny; třísla; Female; Humans; Groin; nádory vulvy; Vulvar Neoplasms; ženské pohlaví; lymfatické cévy